2008
DOI: 10.1507/endocrj.k07e-065
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Results in Small Dense LDL Independent of IRS Traits and Hypertriglyceridemia

Abstract: Abstract. There is evidence of an association between hypothyroidism and coronary heart disease. We decided to look at the relationship between hypothyroidism and LDL subclasses' pattern including small, dense LDL to define a biochemical basis for better management of the CHD risk of these patients. We utilized a case-control design to evaluate differences in lipid parameters between cases and controls. Univariate analysis revealed that many factors were associated with LDL particle size. Binary logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…Results of Abbas et al's study supported an independent association between LDL particle size phenotype, plasma TG and thyroid status [26]. In another study that investigated overt hypothyroid patients, no significant discordance in percentages of B phenotype (predominance of sdLDL-C) compared to the controls was found [30].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Results of Abbas et al's study supported an independent association between LDL particle size phenotype, plasma TG and thyroid status [26]. In another study that investigated overt hypothyroid patients, no significant discordance in percentages of B phenotype (predominance of sdLDL-C) compared to the controls was found [30].…”
Section: Discussionmentioning
confidence: 76%
“…Some studies investigated connection between SHypo and dyslipidemia with heterogeneous results. In a crosssectional study of 1149 women aged ≥ 55 years and in large studies subjects with subclinical hypothyroidism had a significantly higher prevalence of CHD than in euthyroid subjects [14,26]. The initial analysis of the Whickham Survey found no association between autoimmune thyroid disease and SHypo over 20 years of follow-up, but re-analysis of the data, looking specifically at individuals with SHypo found an increase in CHD events and mortality [27].…”
Section: Discussionmentioning
confidence: 99%
“…A period of 4-6 weeks of thyroxin replacement therapy is usually needed to correct dyslipidemia in overt hypothyroidism. A study in newly-diagnosed hypothyroid patients showed a decrease in serum TC and LDL levels after thyroxine treatment [8]. But no clear consensus has been established regarding the treatment of SH subjects [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…5 Though a recent study conducted on newly diagnosed hypothyroid patients showed an association between hypothyroidism and elevated LDL, other studies could not conclusively prove such an association. 29,30,31 All these results reiterate the need for studies on the association of fasting Lipid levels with SCH. In our study, we have attempted to bridge this gap and from our results, it could be speculated that though serum LDL-C was higher in SCH subjects and useful cholesterol HDL was comparatively low.…”
Section: Discussionmentioning
confidence: 75%